Prevalence of Brugada-type ECG pattern and early ventricular repolarization pattern in Tunisian athletes - Ouali,Sana; Salem,Helmi Ben; Hammas,Sami; Neffeti,Elyes; Remedi,Fahmi; Mahdhaoui,Abdallah; Boughzala,Essia; Mankai,Rafik (Open Access Journal of Sports Medicine, 2011)
Sana Ouali1, Helmi Ben Salem1, Sami Hammas1, Elyes Neffeti1, Fahmi Remedi1, Abdallah Mahdhaoui2, Essia Boughzela1, Rafik Mankai31Department of Cardiology, Sahloul Hospital, Sousse, Tunisia; 2Department of Cardiology, Farhat Hached, Sousse, Tunisia; 3Central Sports Medicine Centre of El Menzah, TunisiaIntroduction: No data regarding the prevalence of the Brugada-type electrocardiogram (ECG) pattern and the early ventricular repolarization pattern (ERP) in the North African population were available. The aims of this study were to determine the frequency of Brugada-type ECG pattern and ERP in Tunisia and to evaluate ECG descriptors of ventricular repolarization in a population of athletes.Methods: Over a 2-year period, resting 12-lead ECG recordings were analyzed from athletes (n = 540; 348 males; age 18.3 ± 2.4 years). Brugada-type ECG pattern was defined as Type 1, 2, or 3, and ERP was characterized by an elevation of the J point in the inferior and/or lateral leads. The population was divided into three groups of athletes: ERP group; Brugada-type ECG pattern group; and control group, with neither ERP nor Brugada ECG pattern. Clinical and electrocardiographic parameters were compared among the study groups.Results: Nine subjects (1.66%) had a Brugada-type ECG pattern. None of them had the coved-type, 3 (0.6%) had the Type 2, and 6 (1.1%) had the Type 3. All subjects were asymptomatic. A Brugada-type ECG pattern was observed in seven males. No female had the Type 2 Brugada ECG pattern. ECG parameters were similar among Brugada-type ECG pattern and control athletes. ERP (119 subjects, 22%) was obtained in 98 males. Heart rate was lower, the QRS duration shorter and QT and Tpeak–Tend intervals were longer in ERP than control groups.Conclusion: The results indicate that the frequency of the Brugada-type ECG pattern and ERP were respectively 1.66% and 22.00% in athletes, being more prevalent in males. The ERP group experienced shorter QRS duration and longer Tpeak–Tend interval than in the control ...